Fresno County Legal Services at 906 N Street - Watkins, Howard::::::::: (1978)
Elaine Harris,?, ?, Dave Brodie, Catalina Peralta, William Leifer, Mary Ludy, Bob Higgins, Cris Perez, Virginia Salmeron, Charles Kahill, Alice Gutierrez, Gloria Escalante